Interface conductive type carbon coating slurry and its preparation method and application
Patent Information
- Application Number
- CN202610946457.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-29
- Publication Date
- 2026-08-28
AI Technical Summary
这些杂质相导电性差,在涂炭层与铝基体之间形成电子传输壁垒,导致界面接触电阻增高;高的界面电阻会引起电池极化增大、产热增加,严重损害电池的倍率性能、首效和循环寿命
1、本发明采用纳米金属镁作为涂炭浆料功能性添加剂,利用镁的强还原性,在涂布烘干阶段与铝箔表面的绝缘氧化铁等杂质发生固态置换反应,原位生成高导电的纳米金属铁颗粒,这些新生的铁颗粒在涂炭层与铝箔基材界面处形成三维导电桥网络,将原本高电阻的金属-绝缘体-碳接触转变为低电阻的金属-金属-碳接触。
Smart Images

Figure CN122658730A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, specifically to an interface-enhanced carbon coating slurry, its preparation method, and its application. Background Technology
[0002] Aluminum foil is widely used as a current collector in lithium-ion batteries due to its excellent conductivity, ductility, and electrochemical stability. To reduce interfacial impedance, enhance adhesion, and improve corrosion resistance, a carbon coating layer composed of conductive carbon materials such as carbon black, graphite, and a binder is often applied to the surface of the aluminum foil. However, aluminum foil inevitably contains impurity elements such as Fe (iron), Si (silicon), and Cu (copper), which typically exist on the surface in the form of oxides. These impurity phases have poor conductivity and form electron transport barriers between the carbon coating layer and the aluminum substrate, leading to increased interfacial contact resistance. High interfacial resistance causes increased battery polarization and heat generation, severely impairing the battery's rate performance, initial efficiency, and cycle life.
[0003] Currently, most methods for improving interfacial conductivity focus on optimizing the slurry itself, such as using carbon materials with higher conductivity or performing complex pretreatments on aluminum foil, such as pickling and plasma treatment. These methods are either costly or complex, and they fail to fundamentally solve the problems caused by impurities at the interface.
[0004] In summary, the preparation of an interface-enhanced carbon coating slurry is of great significance in order to solve the above problems. Summary of the Invention
[0005] The purpose of this invention is to provide an interface-enhanced conductive carbon coating slurry, its preparation method, and its application, so as to solve the problems mentioned in the background art.
[0006] To solve the above-mentioned technical problems, the present invention provides the following technical solution: An interface-enhancing carbon coating slurry includes a conductive agent, a binder, a pH adjuster, a wetting agent, a solvent, and functional additives; The functional additive is one or more of nano-metals, organometallic compounds, and organic acid salts.
[0007] Ideally, in organometallic compounds, the metal component is one of iron, cobalt, or nickel.
[0008] In the above technical solution, the functional additives can chemically react with impurity elements such as iron and silicon on the surface of aluminum foil, and generate substances with higher conductivity than the original impurities in situ at the interface, such as elemental metals, conductive carbides, and alloy phases, thereby reducing the interface penetration resistance.
[0009] Ideally, the functional additive is nano-sized magnesium.
[0010] Ideally, the median particle size of the nano-sized magnesium is ≤100 nm.
[0011] Ideally, the functional additive is iron acetylacetone.
[0012] In a more optimized manner, the solid components of the carbon coating slurry include the following components by mass percentage: 50-67% conductive agent, 30-47% binder solid components, 1% pH adjuster solid components, and 2-6% functional additives.
[0013] Ideally, the solvent for the carbon coating slurry is deionized water.
[0014] Ideally, the conductive agent is a mixture of carbon black and graphite, with a mass ratio of carbon black to graphite of (1-2):1.
[0015] Ideally, the adhesive is a polyacrylic acid liquid with a solid content of 15-25% and a viscosity of 800-3000 mPa·s.
[0016] Ideally, the pH adjuster is a sodium hydroxide solution with a concentration of 1-1.2 mol / L.
[0017] Ideally, isopropanol should be used as the wetting agent.
[0018] A method for preparing an interface-enhanced carbon coating slurry includes the following steps: (1) Mix 70-80% of the mass of deionized water with the binder and disperse at 1000-1200 rpm for 30-45 min; Then add the functional additives and disperse at 2000-2200 rpm for 10-15 minutes; Add 50-60% of the conductive agent by mass and disperse at 1500-1800 rpm for 30-45 min; add the remaining conductive agent and disperse at 2000-2600 rpm for 30-45 min. Add the remaining components to deionized water and disperse at 2000-2600 rpm for 30-45 min; Add a pH adjuster to adjust the pH of the slurry to 6-8; Add wetting agent, stir at 10-15 rpm for 30-45 minutes, and then discharge. (2) Homogenize the slurry in a homogenizer at a pressure of 500-600 bar 2-3 times to obtain carbon coating slurry.
[0019] Ideally, the solids content of the carbon coating slurry should be 8-12%.
[0020] Ideally, the amount of wetting agent added should be 8-10% of the total mass of the carbon coating slurry.
[0021] An application of an interface-enhancing carbon coating slurry for preparing a carbon-coated current collector includes the following steps: coating the carbon coating slurry onto the surface of the current collector, subjecting it to gradient drying and cooling to form a carbon coating layer, thereby obtaining a carbon-coated current collector.
[0022] Ideally, the current collector is made of aluminum foil with a width of 300 mm and a thickness of 12 μm. The coating is performed using a slot extrusion coating machine with a coating line speed of 80-100m / min and a coating width of 300-350mm. The gradient drying uses a four-section series drying oven with a coating line speed of 80-100m / min. The temperature of each section of the oven is set as follows: the first section is 90℃, the second section is 110℃, the third section is 100℃, and the fourth section is 95℃. The cooling process employs a cooling roller, with the following conditions: the surface temperature of the cooling roller is 10-25°C, the cooling medium is circulating cooling water, the contact time between the carbon-coated aluminum foil and the cooling roller is 0.5-3 seconds, and the bonding pressure of the cooling roller on the carbon coating layer is 0.1-0.5 MPa. After cooling by the cooling roller, the surface temperature of the carbon-coated aluminum foil drops below 35°C, and then it is wound up.
[0023] Ideally, the thickness of the carbon coating layer is 0.9-1.2 μm.
[0024] Compared with the prior art, the beneficial effects achieved by the present invention are: 1. This invention uses nano-magnesium metal as a functional additive in the carbon coating slurry. Taking advantage of magnesium's strong reducing properties, it undergoes a solid-state displacement reaction with impurities such as insulating iron oxide on the aluminum foil surface during the coating and drying stage, generating highly conductive nano-iron metal particles in situ. These newly formed iron particles form a three-dimensional conductive bridge network at the interface between the carbon coating layer and the aluminum foil substrate, transforming the original high-resistance metal-insulator-carbon contact into a low-resistance metal-metal-carbon contact.
[0025] 2. This invention uses ferric acetylacetonate as a functional additive in the carbon coating slurry. During the coating and drying process, under the combined effects of nanoscale dispersion and the slurry environment, the pyrolysis initiation temperature of ferric acetylacetonate is significantly reduced, allowing for partial pyrolysis to generate highly active nano-iron-containing intermediates, forming an initial conductive network. Subsequently, under the continuous thermal action of the positive electrode baking process and the battery formation stage, these iron-containing intermediates are further transformed into nano-α-iron particles. Since the aforementioned iron-containing species are all at the nanoscale, with large specific surface area, high surface atomic ratio, and high catalytic activity, they can catalyze the low-temperature catalytic reaction between carbon in the carbon coating slurry and impurities such as iron and silicon on the aluminum foil surface at temperatures far lower than those of traditional carbothermal reduction reactions, continuously generating more conductive iron and silicon elements, thereby gradually building and enhancing the composite conductive network at the interface.
[0026] 3. This invention transforms impurity points, which are inherently conductive defects, into highly conductive advantageous nodes by designing in-situ reactions between functional additives and impurity elements on the aluminum foil surface, thereby fundamentally reducing interfacial resistance. Compared to carbonized current collectors prepared without functional additives in the carbonized slurry, the carbonized current collector prepared with the carbonized slurry of this invention exhibits significantly reduced carbon layer resistance. Lithium-ion batteries prepared based on the carbonized current collector show significantly improved first-cycle efficiency and 2000-cycle capacity retention. The functional additives of this invention can be directly added to existing aqueous carbonized slurry formulations without significant changes to the coating and drying processes, facilitating industrialization. This invention provides two preferred schemes: a direct reduction pathway based on nano-metallic magnesium and a catalytic pathway based on the organometallic salt acetylacetone iron, offering options for different production conditions. This invention has low production and maintenance costs, making it easy to promote and use. Attached Figure Description
[0027] Figure 1 Image 1 shows the EDS layering inside the carbon coating layer in Embodiment 2 of the present invention. Figure 2 Image 2 shows the EDS layered image of the interface between the carbon coating layer and the aluminum foil current collector in Embodiment 1 of the present invention. Detailed Implementation
[0028] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0029] In the following embodiments, the parts are by weight. It should be noted that there are no special restrictions on the purchase manufacturers of all the raw materials involved in this invention. Exemplary examples include: the binder is polyacrylic acid liquid, model 7002, with a solid content of 25% and a viscosity of 900 mPa·s; the median particle size of the nano-metallic magnesium is 100 nm; the carbon black model is SHYT-150P; the graphite part number is 20019126; the acetylacetone iron part number is XW021402418103; the aluminum foil has a width of 300 mm and a thickness of 12 μm; the remaining raw materials are commercially available.
[0030] Example 1: A method for preparing an interface-enhanced carbon coating slurry, comprising the following steps: (1) Mix 75% by mass of deionized water with the binder and disperse at 1100 rpm for 30 min; Then add the functional additive nano-metallic magnesium and disperse at 2100 rpm for 10 min; Add 50% of the conductive agent by mass and disperse at 1600 rpm for 30 min; add the remaining conductive agent and disperse at 2300 rpm for 30 min; the conductive agent is a mixture of carbon black and graphite, with a mass ratio of carbon black to graphite of 1:1. Add the remaining components to deionized water and disperse at 2300 rpm for 30 min; Add sodium hydroxide solution as a pH adjuster to adjust the pH of the slurry to 7; the concentration of the sodium hydroxide solution is 1 mol / L. Add isopropanol as a wetting agent at 10% of the total mass of the carbon coating slurry, stir at 12 rpm for 40 minutes, and then discharge. (2) The slurry was homogenized twice in a homogenizer at a pressure of 600 bar to obtain a carbon coating slurry with a solid content of 10%; The solid components of the carbon coating slurry include the following components by mass percentage: 63% conductive agent, 30% binder solid components, 1% pH adjuster solid components, and 6% functional additives. The carbon coating slurry is used to prepare the carbon-coated current collector, which includes the following steps: coating the carbon coating slurry onto the surface of the aluminum foil current collector, drying it through a gradient and cooling it with a cooling roller to form a carbon coating layer with a thickness of 1μm, thereby obtaining the carbon-coated current collector; The coating is performed using a slot extrusion coating machine with a coating line speed of 90m / min and a coating width of 300mm. The gradient drying uses a four-section series drying oven with a coating line speed of 90m / min. The temperature of each section of the oven is set as follows: the first section is 90℃, the second section is 110℃, the third section is 100℃, and the fourth section is 95℃. The cooling roller cooling process conditions are as follows: the surface temperature of the cooling roller is 15℃, the cooling medium is circulating cooling water; the contact time between the carbon-coated aluminum foil and the cooling roller is 1s, and the bonding pressure of the cooling roller on the carbon coating layer is 0.3MPa; after cooling by the cooling roller, the surface temperature of the carbon-coated aluminum foil drops to 35℃, and then it is wound up.
[0031] Example 2: A method for preparing an interface-enhanced carbon coating slurry, comprising the following steps: (1) Mix 75% by mass of deionized water with the binder and disperse at 1100 rpm for 30 min; Then add the functional additive acetylacetone iron and disperse at 2100 rpm for 10 min; Add 50% of the conductive agent by mass and disperse at 1600 rpm for 30 min; add the remaining conductive agent and disperse at 2300 rpm for 30 min; the conductive agent is a mixture of carbon black and graphite, with a mass ratio of carbon black to graphite of 1:1. Add the remaining components to deionized water and disperse at 2300 rpm for 30 min; Add sodium hydroxide solution as a pH adjuster to adjust the pH of the slurry to 7; the concentration of the sodium hydroxide solution is 1 mol / L. Add isopropanol as a wetting agent at 10% of the total mass of the carbon coating slurry, stir at 12 rpm for 40 minutes, and then discharge. (2) The slurry was homogenized twice in a homogenizer at a pressure of 600 bar to obtain a carbon coating slurry with a solid content of 10%; The solid components of the carbon coating slurry include the following components by mass percentage: 63% conductive agent, 30% binder solid components, 1% pH adjuster solid components, and 6% functional additives. The carbon coating slurry is used to prepare the carbon-coated current collector, which includes the following steps: coating the carbon coating slurry onto the surface of the aluminum foil current collector, drying it through a gradient and cooling it with a cooling roller to form a carbon coating layer with a thickness of 1μm, thereby obtaining the carbon-coated current collector; The coating is performed using a slot extrusion coating machine with a coating line speed of 90m / min and a coating width of 300mm. The gradient drying uses a four-section series drying oven with a coating line speed of 90m / min. The temperature of each section of the oven is set as follows: the first section is 90℃, the second section is 110℃, the third section is 100℃, and the fourth section is 95℃. The cooling roller cooling process conditions are as follows: the surface temperature of the cooling roller is 15℃, the cooling medium is circulating cooling water; the contact time between the carbon-coated aluminum foil and the cooling roller is 1s, and the bonding pressure of the cooling roller on the carbon coating layer is 0.3MPa; after cooling by the cooling roller, the surface temperature of the carbon-coated aluminum foil drops to 35℃, and then it is wound up.
[0032] Example 3: A method for preparing an interface-enhanced carbon coating slurry, comprising the following steps: (1) Mix 75% by mass of deionized water with the binder and disperse at 1100 rpm for 30 min; Then add the functional additive nano-metallic magnesium and disperse at 2100 rpm for 10 min; Add 50% of the conductive agent by mass and disperse at 1600 rpm for 30 min; add the remaining conductive agent and disperse at 2300 rpm for 30 min; the conductive agent is a mixture of carbon black and graphite, with a mass ratio of carbon black to graphite of 1:1. Add the remaining components to deionized water and disperse at 2300 rpm for 30 min; Add sodium hydroxide solution as a pH adjuster to adjust the pH of the slurry to 7; the concentration of the sodium hydroxide solution is 1 mol / L. Add isopropanol as a wetting agent at 10% of the total mass of the carbon coating slurry, stir at 12 rpm for 40 minutes, and then discharge. (2) The slurry was homogenized twice in a homogenizer at a pressure of 600 bar to obtain a carbon coating slurry with a solid content of 10%; The solid components of the carbon coating slurry include the following components by mass percentage: 64% conductive agent, 30% binder solid components, 1% pH adjuster solid components, and 5% functional additives. The carbon coating slurry is used to prepare the carbon-coated current collector, which includes the following steps: coating the carbon coating slurry onto the surface of the aluminum foil current collector, drying it through a gradient and cooling it with a cooling roller to form a carbon coating layer with a thickness of 1μm, thereby obtaining the carbon-coated current collector; The coating is performed using a slot extrusion coating machine with a coating line speed of 90m / min and a coating width of 300mm. The gradient drying uses a four-section series drying oven with a coating line speed of 90m / min. The temperature of each section of the oven is set as follows: the first section is 90℃, the second section is 110℃, the third section is 100℃, and the fourth section is 95℃. The cooling roller cooling process conditions are as follows: the surface temperature of the cooling roller is 15℃, the cooling medium is circulating cooling water; the contact time between the carbon-coated aluminum foil and the cooling roller is 1s, and the bonding pressure of the cooling roller on the carbon coating layer is 0.3MPa; after cooling by the cooling roller, the surface temperature of the carbon-coated aluminum foil drops to 35℃, and then it is wound up.
[0033] Example 4: A method for preparing an interface-enhanced carbon coating slurry, comprising the following steps: (1) Mix 75% by mass of deionized water with the binder and disperse at 1100 rpm for 30 min; Then add the functional additive acetylacetone iron and disperse at 2100 rpm for 10 min; Add 50% of the conductive agent by mass and disperse at 1600 rpm for 30 min; add the remaining conductive agent and disperse at 2300 rpm for 30 min; the conductive agent is a mixture of carbon black and graphite, with a mass ratio of carbon black to graphite of 1:1. Add the remaining components to deionized water and disperse at 2300 rpm for 30 min; Add sodium hydroxide solution as a pH adjuster to adjust the pH of the slurry to 7; the concentration of the sodium hydroxide solution is 1 mol / L. Add isopropanol as a wetting agent at 10% of the total mass of the carbon coating slurry, stir at 12 rpm for 40 minutes, and then discharge. (2) The slurry was homogenized twice in a homogenizer at a pressure of 600 bar to obtain a carbon coating slurry with a solid content of 10%; The solid components of the carbon coating slurry include the following components by mass percentage: 64% conductive agent, 30% binder solid components, 1% pH adjuster solid components, and 5% functional additives. The carbon coating slurry is used to prepare the carbon-coated current collector, which includes the following steps: coating the carbon coating slurry onto the surface of the aluminum foil current collector, drying it through a gradient and cooling it with a cooling roller to form a carbon coating layer with a thickness of 1μm, thereby obtaining the carbon-coated current collector; The coating is performed using a slot extrusion coating machine with a coating line speed of 90m / min and a coating width of 300mm. The gradient drying uses a four-section series drying oven with a coating line speed of 90m / min. The temperature of each section of the oven is set as follows: the first section is 90℃, the second section is 110℃, the third section is 100℃, and the fourth section is 95℃. The cooling roller cooling process conditions are as follows: the surface temperature of the cooling roller is 15℃, the cooling medium is circulating cooling water; the contact time between the carbon-coated aluminum foil and the cooling roller is 1s, and the bonding pressure of the cooling roller on the carbon coating layer is 0.3MPa; after cooling by the cooling roller, the surface temperature of the carbon-coated aluminum foil drops to 35℃, and then it is wound up.
[0034] Example 5: A method for preparing an interface-enhanced carbon coating slurry, comprising the following steps: (1) Mix 75% by mass of deionized water with the binder and disperse at 1100 rpm for 30 min; Then add the functional additive nano-metallic magnesium and disperse at 2100 rpm for 10 min; Add 50% of the conductive agent by mass and disperse at 1600 rpm for 30 min; add the remaining conductive agent and disperse at 2300 rpm for 30 min; the conductive agent is a mixture of carbon black and graphite, with a mass ratio of carbon black to graphite of 1:1. Add the remaining components to deionized water and disperse at 2300 rpm for 30 min; Add sodium hydroxide solution as a pH adjuster to adjust the pH of the slurry to 7; the concentration of the sodium hydroxide solution is 1 mol / L. Add isopropanol as a wetting agent at 10% of the total mass of the carbon coating slurry, stir at 12 rpm for 40 minutes, and then discharge. (2) The slurry was homogenized twice in a homogenizer at a pressure of 600 bar to obtain a carbon coating slurry with a solid content of 10%; The solid components of the carbon coating slurry include the following components by mass percentage: 65% conductive agent, 30% binder solid components, 1% pH adjuster solid components, and 4% functional additives. The carbon coating slurry is used to prepare the carbon-coated current collector, which includes the following steps: coating the carbon coating slurry onto the surface of the aluminum foil current collector, drying it through a gradient and cooling it with a cooling roller to form a carbon coating layer with a thickness of 1μm, thereby obtaining the carbon-coated current collector; The coating is performed using a slot extrusion coating machine with a coating line speed of 90m / min and a coating width of 300mm. The gradient drying uses a four-section series drying oven with a coating line speed of 90m / min. The temperature of each section of the oven is set as follows: the first section is 90℃, the second section is 110℃, the third section is 100℃, and the fourth section is 95℃. The cooling roller cooling process conditions are as follows: the surface temperature of the cooling roller is 15℃, the cooling medium is circulating cooling water; the contact time between the carbon-coated aluminum foil and the cooling roller is 1s, and the bonding pressure of the cooling roller on the carbon coating layer is 0.3MPa; after cooling by the cooling roller, the surface temperature of the carbon-coated aluminum foil drops to 35℃, and then it is wound up.
[0035] Example 6: A method for preparing an interface-enhanced carbon coating slurry, comprising the following steps: (1) Mix 75% by mass of deionized water with the binder and disperse at 1100 rpm for 30 min; Then add the functional additive acetylacetone iron and disperse at 2100 rpm for 10 min; Add 50% of the conductive agent by mass and disperse at 1600 rpm for 30 min; add the remaining conductive agent and disperse at 2300 rpm for 30 min; the conductive agent is a mixture of carbon black and graphite, with a mass ratio of carbon black to graphite of 1:1. Add the remaining components to deionized water and disperse at 2300 rpm for 30 min; Add sodium hydroxide solution as a pH adjuster to adjust the pH of the slurry to 7; the concentration of the sodium hydroxide solution is 1 mol / L. Add isopropanol as a wetting agent at 10% of the total mass of the carbon coating slurry, stir at 12 rpm for 40 minutes, and then discharge. (2) The slurry was homogenized twice in a homogenizer at a pressure of 600 bar to obtain a carbon coating slurry with a solid content of 10%; The solid components of the carbon coating slurry include the following components by mass percentage: 65% conductive agent, 30% binder solid components, 1% pH adjuster solid components, and 4% functional additives. The carbon coating slurry is used to prepare the carbon-coated current collector, which includes the following steps: coating the carbon coating slurry onto the surface of the aluminum foil current collector, drying it through a gradient and cooling it with a cooling roller to form a carbon coating layer with a thickness of 1μm, thereby obtaining the carbon-coated current collector; The coating is performed using a slot extrusion coating machine with a coating line speed of 90m / min and a coating width of 300mm. The gradient drying uses a four-section series drying oven with a coating line speed of 90m / min. The temperature of each section of the oven is set as follows: the first section is 90℃, the second section is 110℃, the third section is 100℃, and the fourth section is 95℃. The cooling roller cooling process conditions are as follows: the surface temperature of the cooling roller is 15℃, the cooling medium is circulating cooling water; the contact time between the carbon-coated aluminum foil and the cooling roller is 1s, and the bonding pressure of the cooling roller on the carbon coating layer is 0.3MPa; after cooling by the cooling roller, the surface temperature of the carbon-coated aluminum foil drops to 35℃, and then it is wound up.
[0036] Example 7: Based on Example 1, the amount of functional additive nano-metallic magnesium added is 3%, and the amount of conductive agent added is 66%; the rest is the same as in Example 1.
[0037] Example 8: Based on Example 1, the functional additive is ferric acetylacetone, with an addition amount of 3%, and the conductive agent addition amount is 66%; the rest is the same as in Example 1.
[0038] Example 9: Based on Example 1, the amount of functional additive nano-metallic magnesium added is 2%, and the amount of conductive agent added is 67%; the rest is the same as in Example 1.
[0039] Example 10: Based on Example 1, the functional additive is ferric acetylacetone, with an addition amount of 2%, and the conductive agent addition amount is 67%; the rest is the same as in Example 1.
[0040] Comparative Example 1: Based on Example 1, no functional additives were used, and the amount of conductive agent added was 69%; the rest was the same as in Example 1.
[0041] Testing experiment: Transmission resistance test: Take the carbon-coated current collectors prepared in Examples 1-10 and Comparative Example 1, cut them into 5×5cm samples, test the transmission resistance under a film resistance meter, and record the test data. Battery initial efficiency and cycle stability tests: ① Preparation of positive electrode sheet: Iron phosphate positive electrode active material, conductive carbon black, and binder polyvinylidene fluoride are mixed evenly in a mass ratio of 96:2:2 and dispersed in the solvent N-methylpyrrolidone to prepare positive electrode slurry; the positive electrode slurry is evenly coated on both surfaces of the positive electrode current collector and carbon-coated current collector to form a positive electrode active coating, dried at 120℃ for 8 hours in a vacuum environment, and then cold-pressed and slit to obtain the positive electrode sheet; ② Preparation of negative electrode sheet: Graphite negative electrode active material, conductive carbon black, Li4Ti5O 12 The negative electrode slurry was prepared by mixing the positive and negative electrode sheets in a mass ratio of 93:5:2 and dispersing them in deionized water. The negative electrode slurry was then coated onto a carbon-coated current collector using a doctor blade and dried at 120°C for 4 hours to obtain the negative electrode sheet. ③ Preparation of lithium-ion batteries: The positive and negative electrode sheets were stacked in sequence and injected with electrolyte. After vacuum sealing, settling, formation, and shaping, lithium-ion batteries were obtained. ④ Assembly and testing of batteries: The lithium-ion batteries of each embodiment and comparative example were tested at room temperature, with 0.2C and 0. The lithium-ion battery was charged at constant current and constant voltage rates of 3C, 0.5C, 1C, 2C, 3C, and 5C to 3-4.5V, with a cutoff current of 0.15-3A. Then, the lithium-ion battery was discharged at constant current rates of 0.2C, 0.3C, 0.5C, 1C, 2C, 3C, and 5C to 3-4.5V. This constituted one charge-discharge cycle. The lithium-ion battery was charged and discharged 2000 times in the above manner. The initial efficiency of the lithium-ion battery at 0.2C rate and the capacity retention rate after 2000 cycles at 1C rate were tested.
[0042]
[0043]
[0044]
[0045] Conclusion: The data in Table 1 show that: This invention introduces nano-sized magnesium as a functional additive into the carbon coating slurry of Examples 1, 3, 5, 7, and 9, and introduces iron acetylacetone as a functional additive into the carbon coating slurry of Examples 2, 4, 6, 8, and 10. This enables in-situ reaction with impurity elements on the aluminum foil surface during the coating and drying process, generating a highly conductive new phase. This significantly reduces the interfacial penetration resistance of the carbon-coated aluminum foil and improves the first charge-discharge efficiency and cycle stability of the lithium-ion battery.
[0046] Data from Examples 1-10 show that when the functional additive is nano-metallic magnesium, the overall performance is better than that of iron acetylacetone. The effect is best when the amount of functional additive added is 6% of the total solid mass. As the amount of functional additive added decreases, the performance gradually deteriorates, but it is still significantly better than that of Comparative Example 1 without functional additive.
[0047] Comparative Example 1, based on Example 1, did not use functional additives and its performance was significantly inferior to that of Example 1, demonstrating that the functional additives of the present invention are a key factor in improving interfacial conductivity and battery performance.
[0048] In Tables 2 and 3, Table 2 shows the EDS energy dispersive spectroscopy analysis performed inside the carbon coating layer in Example 2. The electron beam did not penetrate the carbon coating layer, and only the coating components were detected, so there was no Al element. In addition, the detection location was inside the carbon coating layer, so the C element content was significantly higher than the C element content in Table 3. Furthermore, the functional additive used in Example 2 was acetylacetone iron, so the Fe element content was significantly higher than the Fe element content in Table 3. The F and P elements in Table 2 originated from impurities carried in the raw materials used in the carbon coating slurry. In order to improve the conductivity of the binder, P element was added to the polyacrylic acid adhesive. The presence of acetylacetone iron promoted the enrichment of P-containing impurities on the surface of the analysis area or local micro-uniform distribution, resulting in the capture of a higher concentration of P signal at this test point. Table 3 shows the EDS energy dispersive spectroscopy analysis at the interface between the carbon coating layer and the aluminum foil current collector in Example 1. The electron beam penetrated the carbon coating layer and reached the aluminum foil substrate, so a large amount of Al was detected. In addition, the electron beam penetrated the alumina layer on the surface of the aluminum foil, so the O content was significantly higher than that in Table 2. The Fe element in Table 3 comes from trace impurities on the surface of the aluminum foil. After the nano-magnesium replacement reaction, very little remains. The low Fe content precisely proves the high efficiency of the nano-magnesium scheme. The F element in Table 3 comes from impurities carried in the raw materials used in the carbon coating slurry. The addition of nano-magnesium changed the chemical environment of the slurry, so that the P-containing impurities were not enriched in the EDS analysis area. At the same time, the analysis area in Table 3 has penetrated to the aluminum foil substrate. The dilution effect of the Al signal may also make the trace P signal below the detection limit.
[0049] Depend on Figure 1 As shown in Table 2, in the carbon-coated current collector using acetylacetone iron as a functional additive, the analysis area is located inside or on the surface of the carbon coating layer. Furthermore, up to 27.85% of the Fe element in Table 2 directly originates from the nano-sized iron particles generated during the decomposition of the acetylacetone iron additive during drying, while 22.47% of the C element comes from the carbon black and graphite conductive agent in the carbon coating layer. These in-situ generated and uniformly distributed nano-iron particles, acting as a highly conductive phase, together with the conductive carbon material, construct a three-dimensional conductive network, thereby significantly reducing the interfacial penetration resistance between the carbon coating layer and the aluminum foil, and improving the initial coulombic efficiency and 2000-cycle capacity retention of the lithium battery.
[0050] Depend on Figure 2 As shown in Table 3, EDS energy dispersive spectroscopy and elemental surface scanning were performed on the carbon-coated current collector prepared in Example 1. The EDS analysis results are shown in Table 2. C, O, Al, and Fe elements were detected simultaneously at the interface between the carbon coating layer and the aluminum foil current collector. The presence of Al indicates that the analysis area reached the surface of the aluminum foil current collector. Figure 2 The elemental distribution map shows that Al is continuously and uniformly distributed within the scanning area, confirming that the EDS analysis location is the actual interface between the carbon coating layer and the aluminum foil current collector. The detected Fe element comes from impurities on the aluminum foil surface, rather than external contamination.
[0051] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.
Claims
1. An interface-enhanced conductive carbon coating slurry, characterized in that: This includes conductive agents, binders, pH adjusters, wetting agents, solvents, and functional additives; The functional additive is one or more of nano-metals, organometallic compounds, and organic acid salts.
2. The interface-enhancing conductive carbon coating slurry according to claim 1, characterized in that: The functional additive is nano-sized magnesium.
3. The interface-enhancing conductive carbon coating slurry according to claim 1, characterized in that: The functional additive is iron acetylacetone.
4. The interface-enhancing conductive carbon coating slurry according to claim 1, characterized in that: The solid components of the carbon coating slurry include the following components by mass percentage: 50-67% conductive agent, 30-47% binder solid components, 1% pH adjuster solid components, and 2-6% functional additives.
5. The interface-enhancing conductive carbon coating slurry according to claim 1, characterized in that: The conductive agent is a mixture of carbon black and graphite, with a mass ratio of carbon black to graphite of (1-2):
1.
6. The interface-enhancing conductive carbon coating slurry according to claim 1, characterized in that: The adhesive is a polyacrylic acid liquid with a solid content of 15-25% and a viscosity of 800-3000 mPa·s.
7. The interface-enhancing conductive carbon coating slurry according to claim 1, characterized in that: The pH adjuster is a sodium hydroxide solution with a concentration of 1-1.2 mol / L.
8. A method for preparing an interface-enhanced conductive carbon coating slurry, characterized in that: Includes the following steps: (1) Mix 70-80% of the mass of deionized water with the binder and disperse at 1000-1200 rpm for 30-45 min; Then add the functional additives and disperse at 2000-2200 rpm for 10-15 minutes; Add 50-60% of the conductive agent by mass and disperse at 1500-1800 rpm for 30-45 min; add the remaining conductive agent and disperse at 2000-2600 rpm for 30-45 min. Add the remaining components to deionized water and disperse at 2000-2600 rpm for 30-45 min; Add a pH adjuster to adjust the pH of the slurry to 6-8; Add wetting agent, stir at 10-15 rpm for 30-45 minutes, and then discharge. (2) Homogenize the slurry in a homogenizer at a pressure of 500-600 bar 2-3 times to obtain carbon coating slurry.
9. An application of an interface-enhancing conductive carbon coating slurry, characterized in that: The method for preparing a carbon-coated current collector includes the following steps: applying a carbon-coated slurry prepared by the method of claim 8 onto the surface of the current collector, followed by gradient drying and cooling to form a carbon-coated layer, thereby obtaining a carbon-coated current collector.
10. The application of the interface-enhancing carbon coating slurry according to claim 9, characterized in that: The current collector is made of aluminum foil; The coating is performed using a slot extrusion coating machine with a coating line speed of 80-100m / min; The gradient drying uses a four-section series drying oven with a coating line speed of 80-100m / min. The temperature of each section of the oven is set as follows: the first section is 90℃, the second section is 110℃, the third section is 100℃, and the fourth section is 95℃.